Heartfulness Meditation: A Yogic and Neuroscientific Perspective - van’t Westeinde, Annelies; Patel, Kamlesh D. (Frontiers in Psychology, 2022)
Today, as research into the contemplative sciences is being widely referenced, the research community would benefit from an understanding of the Heartfulness method of meditation. Heartfulness offers an in-depth experiential practice focused on the evolution of human consciousness using the ancient technique of Pranahuti (yogic Transmission) during Meditation, in combination with the more active mental practice of “Cleaning.” Both are enabled by initiation into the Heartfulness practices. These unique features distinguish Heartfulness from other paths that have been described in the scientific literature thus far. In this introductory paper, we present the Heartfulness practices, the philosophy upon which the practices are based, and we reflect on the putative mechanisms through which Heartfulness could exert its effects on the human body and mind in the light of scientific research that has been done in other meditation systems. We conclude with suggestions for future research on the Heartfulness way of meditation.